Regularities of the coatings formation from bronze and babbit powders by hot pressing method - Казимиренко, Юлія Олексіївна; Лебедєва, Наталія Юріївна (Technology audit and production reserves, 2015)
The paper is devoted to the development of new coating made of bronze and babbit powders by hot pressing method. The purpose of the work is to explore the possibility and establish the regularities of coating formation on the surface with use of powders which have been obtained by grinding waste products. The new device for hot-pressing processes which allows you to control shrinkage has been developed for experimental studies. The studies of the coating were carried out by the methods of optical metallography, X-ray analysis, mechanical testing. It is shown that the formation of the structure combines the processes of the liquid phase sintering of the powder mixture and the diffusion interaction with tinned of steel surface 20. The structure of coating consists of the bronze solid phase and babbit soft phase that provides wear resistance. The established regularities allow you to control the processes of coating formation, creating permanent connections with the steel surface and using waste products. The developed technology can be used for manufacturing new and for their repair worn details of ship locking reinforcement of cargo systems (flanges, cranes, valves).